Implementasi Mata Kuliah Manajemen Pemasaran Untuk Peningkatan Pendapatan Usaha Rias Salon - Ponco Nofian Mustoro (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Marketing a product at first glance is easy, but it needs the right method of what marketing means that is right on target so that it can be in accordance with the expected goals and get profits or profits as expected, through techniques of fsn the right theories in managing business ventures, especially in marketing management so that in buying and selling goods or services offered by business actors the best ones are actually chosen. The aim of this research is to find out and explain the implementation of the Marketing Management course to increase the income of a Beauty Salon Make-up Business and the factors that can increase the income of a Beauty Salon Make-up business. The research method was carried out through a sociological juridical approach because to find out how far the Implementation of Marketing Management Courses for Increasing Revenue for Make Up Salon Businesses (Case Study of Alumni of the Cosmetology Study Program Alumni of the Social Welfare Academy of Mrs. Kartini Semarang. The increase in the salon make-up business is growing because of the progress of the cosmetic business that is circulating in the market. This is supported by the fact that many women want to look prettier and more attractive, so they go to salons to beautify their facial makeup. Salon make-up business owners to be smarter in managing their business, both the skills of the makeup artist who always keeps abreast of the latest makeup models and modern and adequate make-up equipment according to current developments.